RASSF1A inhibits estrogen receptor alpha expression and estrogen-independent signalling: implications for breast cancer development - Thaler, Sonja; Sleeman, Jonathan P. (Oncogene, 2012)
The Ras association domain family 1 isoform A (RASSF1A) is a tumor suppressor whose inactivation is implicated in the development of many human cancers, including breast carcinomas. Little is known about the tumor-suppressive function of RASSF1A in breast tissue and whether its inactivation is mechanistically involved in the initiation and progression of breast tumors. Here, we show that RASSF1A inhibits breast cancer growth in vivo, and suppresses estrogen receptor (ER alpha) expression and function. Reconstitution of RASSF1A in MCF7 cells led to decreased ER alpha levels and reduced sensitivity to estrogen (E2). Concomitantly, we observed decreased expression of Id1 as well as the E2-responsive genes Bcl-2 and c-Myc that cooperatively contribute to the immortalization and transformation of breast epithelial cells. This downregulation was associated with induction of cell-cycle arrest and senescence that constitute early barriers to cancer initiation and progression. Knockdown of ER alpha showed that downregulation of ER alpha suffices to increase senescence and inhibit expression of Bcl-2, c-Myc and Id1. However, enforced expression of ER alpha only partially rescued RASSF1A-mediated growth inhibition and senescence, suggesting that suppression of ER alpha expression and activity is not the only mechanism by which RASSF1A inhibits growth and survival of breast cancer cells. Ectopic expression of Bcl-2, c-Myc and Id1 had little or no effect on RASSF1A-mediated growth arrest, indicating that RASSF1A acts dominantly over these oncogenes. Mechanistically, RASSF1A was found to suppress ER alpha expression through Akt1. It also transiently inhibited ER alpha-induced Ras-MAPK activity after exposure of cells to E2. Together, our data show that RASSF1A acts as a tumor suppressor in ER alpha+ mammary epithelial cells, in part through inhibiting ER alpha expression and activity. These findings suggest that RASSF1A has a key role in suppressing the transformation of human breast epithelial cells and ER alpha+ breast cancer initiation.
Gesehen am 04.04.2018